Green Financing, Board Gender Diversity, and Firm Value: The Moderating Role of Capital Adequacy Ratio in Indonesian Banks - I Kadek Bagiana; Yura Karlinda Wiasa Putri; M Doni Permana Putra; Ni Gusti Ayu Trisna Pebrianti; I Gusti Agung Mas Tika Purnama Dewi (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study aims to examine the effects of green financing and board gender diversity on firm value, as well as the moderating role of Capital Adequacy Ratio (CAR), in banking companies listed on the Indonesia Stock Exchange during 2021–2024. Design/methodology/approach – This study employs a quantitative explanatory approach using panel data regression analysis. The sample consists of 47 listed banks observed over the 2021–2024 period, resulting in 188 firm-year observations. Firm value is proxied by PBV, while green financing, board gender diversity, and CAR serve as the main explanatory variables. Profitability, non-performing loans, and firm size are included as control variables. Finding/Results – The results show that green financing and CAR have positive and significant effects on firm value. In contrast, board gender diversity has a negative and significant direct effect. The moderating analysis further reveals that CAR weakens the positive effect of green financing on firm value but strengthens the effect of board gender diversity on firm value. Originality/Value – The study contributes to the sustainable finance and corporate governance literature by demonstrating that market valuation in the banking sector is shaped not only by sustainability and diversity initiatives, but also by the bank’s underlying financial capacity. Practically, the findings suggest that banks should enhance the credibility of green financing strategies and ensure that board gender diversity is embedded more substantively within governance structures.